2018
DOI: 10.1371/journal.pone.0202665
|View full text |Cite|
|
Sign up to set email alerts
|

Metabolic syndrome in Xinjiang Kazakhs and construction of a risk prediction model for cardiovascular disease risk

Abstract: BackgroundThe high prevalence of metabolic syndrome (MetS) and cardiovascular diseases (CVD) is observed among Kazakhs in Xinjiang. Because MetS may significantly predict the occurrence of CVD, the inclusion of CVD-related indicators in metabolic network may improve the predictive ability for a CVD-risk model for Kazakhs in Xinjiang.MethodsThe study included 2,644 subjects who were followed for 5 years or longer. CVD cases were identified via medical records of the local hospitals from April 2016 to August 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
2
1
Order By: Relevance
“…The result supported our original hypothesis that the CVD prevalence in Kashgar region was high because of specific lifestyles, lower SES statuses, and less healthcare resources. We were aware of only one prior study performed on Kazakh ethnicity in Kashgar prefecture, and the study reported a higher CVD prevalence than our current estimate (13.9%) [35]. A possible explanation for the discrepancy may be difference in genetic backgrounds; while the study was conducted among Kazakh population, our participants were mainly composed of Uyghur ethnicity.…”
Section: Discussioncontrasting
confidence: 61%
“…The result supported our original hypothesis that the CVD prevalence in Kashgar region was high because of specific lifestyles, lower SES statuses, and less healthcare resources. We were aware of only one prior study performed on Kazakh ethnicity in Kashgar prefecture, and the study reported a higher CVD prevalence than our current estimate (13.9%) [35]. A possible explanation for the discrepancy may be difference in genetic backgrounds; while the study was conducted among Kazakh population, our participants were mainly composed of Uyghur ethnicity.…”
Section: Discussioncontrasting
confidence: 61%
“…A high-fat diet has already resulted in high BMI levels in the sample population (BMI > 24). In addition, a long-term study conducted in Xinjiang indicated that Xinjiang Kazakhs were a high-risk group for metabolic syndrome and cardiovascular diseases [ 30 ]. This further confirmed the negative effects of the above diet structure on the Kazakhs.…”
Section: Discussionmentioning
confidence: 99%
“…The Kazakh ethnicity, as the most populous nomadic ethnic group in Xinjiang, is highly representative among all ethnic groups in Xinjiang. Metabolic syndrome and cardiovascular diseases have been observed among Kazakhs in Xinjiang [9,10], and these data are important in characterising the spectrum of metabolic and cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%